Methods of Foreign Representatives - Shakirova Saida Tuxtajonovna (Genius Journals, 2022)
Language and music have a lot in common in the perception of the brain. Besides the obvious explanation that playing musical instruments develops Broca's area, there is another possibility. As Professor Elbert noted, it is possible that people with a more developed Broca's area are inclined to study music and achieve great success in this. psychological method. 5 hypotheses of psycholinguistics. A description of the psychological schools that determined the development of foreign language teaching methods would be incomplete without Stephen Krashen's psycholinguistic model, which has been extremely popular in the United States over the past two decades.
Keywords: The Acquisition–Learning Hypothesis,; deductive; explicit; formal